Bias-switchable negative and positive photoconductivity in 2D FePS3 ultraviolet photodetectors. (13th April 2018) - Gao, Yi; Lei, Shuijin; Kang, Tingting; Fei, Linfeng; Mak, Chee-Leung; Yuan, Jian; Zhang, Mingguang; Li, Shaojuan; Bao, Qiaoliang; Zeng, Zhongming; Wang, Zhao; Gu, Haoshuang; et al.
Abstract: Metal-phosphorus-trichalcogenides (MPTs), represented by NiPS3, FePS3, etc, are newly developed 2D wide-bandgap semiconductors and have been proposed as excellent candidates for ultraviolet (UV) optoelectronics. In spite of having superior advantages for solar-blind UV photodetectors, including those free of surface trap states, being highly compatible with versatile integrations as well as having an appropriate band gap, to date relevant study is rare. In this work, the photoresponse characteristic of UV detectors based on few-layer FePS3 has been comprehensively investigated. The responsivity of the photodetector, which is observed to be determined by bias gate voltage, may achieve as high as 171.6 mAW −1 under the illumination of 254 nm weak light, which is comparable to most commercial UV detectors. Notably, both negative and positive photoconductivities exist in the FePS3 photodetectors and can be controllably switched with bias voltage. The eminent and novel photoresponse property paves the way for the further development and practical use of 2D MPTs in high-performance UV photodetections.